Incidence and duration of type-specific human papillomavirus infection in high-risk HPV-naïve women: results from the control arm of a phase II HPV-16/18 vaccine trial. Issue 8 (26th August 2016) - Ramanakumar, Agnihotram V; Naud, Paulo; Roteli-Martins, Cecilia M; de Carvalho, Newton S; de Borba, Paola C; Teixeira, Julio C; Blatter, Mark; Moscicki, Anna-Barbara; Harper, Diane M; Romanowski, Barbara; Tyring, Stephen K; Ramjattan, Brian; et al.
Abstract : Objectives: Persistence of human papillomaviruses (HPVs) is necessary for cervical carcinogenesis. We evaluated incidence and duration of type-specific HPV infections and the influence of age and number of sexual partners. Methods: Data were obtained from 553 women (15–25 years), who were seronegative and DNA-negative for high-risk HPV (HR-HPV) types and were enrolled in the placebo arm of a randomised trial of the HPV-16/18 vaccine (NCT00689741 /NCT00120848). They were followed for 6.3 years. Cervicovaginal samples were self-collected at 3-month intervals for up to 27 months, and cervical samples were collected by clinicians at 6-month intervals until study end. Samples were tested for HPV types using a broad-spectrum PCR assay. Incidence rate ratios (RRs) and 95% CIs were used to estimate the association among age, sexual habits and HPV acquisition. Results: Incidence rates (95% CI) using cervical samples were 11.8 (10.4 to 13.4) and 5.6 (4.7 to 6.6) per 1000 women-months for HR-HPVs and low-risk HPVs (LR-HPVs), respectively. Equivalent rates in combined cervicovaginal and cervical samples were 17.2 (15.4 to 19.2) and 6.9 (5.9 to 8.0), respectively. 54 per cent of HR-HPV types from combined cervicovaginal and cervical samples persisted for 1 year compared with 32.3% for LR-HPV types. The risk of acquiring any HPV infection was higher among women aged <21 years (RR=1.33, 95% CI 1.1 to 1.7) and women having >1 sexual partner (RR=1.83, 95% CI 1.4 to 2.4) at baseline. Conclusions: HR-HPV infections were more common and lasted longer on average than LR-HPV infections. HPV acquisition was more common in younger women with multiple sexual partners. Trial registration number: NCT00689741, NCT00120848 ; Post-results.